SISTEM MONITORING JARAK JAUH RADIASI GAMMA SECARA REALTIME BERBASIS WEB SERVER - Habib Sabil Rosyidi; Jatmiko Endro Suseno; Zaenal Arifin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Instruments gamma radiation monitoring system was successfully developed. The instrument can measure the value of radiation exposure in an environment or material. The system was designed using sensor instrumentation Geiger tube M4011 and NGMC Module V1 using a web data base server. Sensor Geiger tube M4011 used had detection capabilities between 0mR / h 120mR / h γRay. Data v alues gamma radiation that has been detected by the sensor is processed by the Geiger tube M4011 Microcontroller Atmega 328. Microcontroller 328 then sends the data that has been read into the webbased database serverusing Internet network GSM. In this system use web interface that allows users to monitor gamma value, without requiring a special receiving station. Basedon the results of validation of the value of gammaray radiation from the Geiger Counter, by means of Geiger Muller standard, Geiger counters and Geiger Muller has value misprint in a row in the lab ecology (4:06 ± 0:21) and (4:08 ± 0.20), at a distance of 4 cm material cesium 137 (9:20 ± 0.20) and (10.2 ± 0:28), and the material cobalt 60 (22:36 ± 0.40) and (22:04 ± 0.36), at a distance of 8 cm material cesium 137 (5.94 ± 0.20) and (5.78 ± 0.21), and materials cobalt 60 (15.96 ± 0.40) and (16:04 ± 12:23), at a distance of 12 cm material cesium 137 (4.76 ± 0:13) and (4:52 ± 0:16), and the material cobalt 60 (11.72 ± 0.21) and (12:46 ± 12:22).